Persepsi dan Risiko QRIS sebagai Alat Transaksi Bagi UMKM - Laylatul Fauziyah; Maretha Ika Prajawati (Universitas Batanghari Jambi, 2023)
Bank Indonesia issued an integrated national payment system, namely the Quick Response Indonesian Standard so that all types of digital payment transactions are properly facilitated. Besides having a myriad of benefits, technology always carries risks. The purpose of this study is to find out and describe the perceptions of MSMEs on the QRIS payment method and also the risks faced by MSME actors who implement the QRIS payment system. This study uses a type of qualitative research. In this study using primary data in the form of interviews with key informants and secondary data in the form of supporting documents. Data collection techniques used were direct field observations, interviews with informants, and documentation. The data analysis technique in this study is interactive which includes data collection, data presentation, data condensation, drawing conclusions, and data verification. The results of the study showed that: Perceptions of Kedai Kopi Janji Jiwa MOG Malang MSMEs on QRIS include perceptions of benefits, perceptions of speed and efficiency and perceptions of ease of use. This shows that MSMEs have a positive perception of QRIS; The risks that are felt by SMEs at Kedai Kopi Janji Jiwa MOG Malang regarding the use of QRIS as a transaction tool are the risk of internet connection and the risk of costs for using QRIS.